Myocardial triggers involved in activation of remote ischaemic preconditioning. Issue 6 (1st May 2016) - Donato, Martín; Goyeneche, María A.; Garces, Mariana; Marchini, Timoteo; Pérez, Virginia; del Mauro, Julieta; Höcht, Christian; Rodríguez, Manuel; Evelson, Pablo; Gelpi, Ricardo J.
Abstract : New Findings: What is the central question of this study? Ischaemia–reperfusion of peripheral tissues protects the heart from subsequent myocardial ischaemia–reperfusion injury, a phenomenon referred to as remote ischaemic preconditioning (rIPC). This study evaluated the possible myocardial triggers of rIPC. What is the main finding and its importance? Remote ischaemic preconditioning reduces infarct size through a vagal pathway and a mechanism involving phosphorylation of Akt and endothelial nitric oxide synthase, opening of mitochondrial ATP‐dependent K + channels and an increase in mitochondrial H2 O2 production. All these phenomena occur before the myocardial ischaemia; hence, they could act as 'triggers' of rIPC. It has been proposed that remote ischaemic preconditioning (rIPC) activates a parasympathetic neural pathway. However, the myocardial intracellular mechanism of rIPC remains unclear. Here, we characterized some of the intracellular signals participating as rIPC triggers. Isolated rat hearts were subjected to 30 min of global ischaemia and 120 min of reperfusion (Non‐rIPC group). In a second group, before the isolation of the heart, an rIPC protocol (three cycles of hindlimb ischaemia–reperfusion) was performed. The infarct size was measured with tetrazolium staining. Expression/phosphorylation of Akt and endothelial nitric oxide synthase (eNOS) and mitochondrial H2 O2 production were evaluated at the end of the rIPC protocol, before myocardial ischaemia–reperfusion. The rIPC significantly decreased the infarct size and induced Akt and eNOS phosphorylation. The protective effect on infarct size was abolished by cervical vagal section, l ‐NAME (an NO synthesis inhibitor) and 5‐hydroxydecanoate (a mitochondrial ATP‐dependent K + channel blocker). Mitochondrial production of H2 O2 was increased by rIPC, whereas it was abolished by cervical vagal section, l ‐NAME and 5‐hydroxydecanoate. We conclude that rIPC activates a parasympathetic vagal pathway and a mechanism involving the phosphorylation of Akt and eNOS, the opening of mitochondrial ATP‐dependent K + channels and the release of H2 O2 by the mitochondria. All these phenomena occur before myocardial ischaemia and could act as triggers of rIPC. Abstract :